UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI CIRI CIRI MAKHLUK HIDUP DI KELAS VII - Indriany, Rini (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This Classroom Action Research was conducted on students in class VII MTs LMD KAWA West Seram District, West Seram Regency with the implementation time on May 11 to 14 of the 2022/2023 Learning year, to find out the objectives: to improve the improvement of the learning process in science subjects carried out by teachers on the material of the characteristics of living things using the Jigsaw type cooperative learning model. The instrument used is the result of data collection on the results of the student work sheet (LKS) test. PTK or commonly called class action research is carried out using simulation observation sheets, and simulation assessment tools as a reflection of learning that has been done both in Cycle I and Cycle II. The results of this study found that learning the Jigsaw Type Cooperative model has advantages, namely: making students able to work together in groups and be responsible for solving problems in the learning process. The results of this study imply that the learning of the Jigsaw Type Cooperative model can make the learning process of science and technology can increase which is brought by the teacher on the material of the characteristics of living things to be better and get an average score of 75.5% in cycle II learning.